ظاهرة الهجرة غير الشرعية (فعالية الإجراءات والقوانين الليبية في مواجهتها) (دراسة مقاصدية): The Phenomenon of Illegal Immigration (the Effectiveness of Libyan Procedures and Laws in Confronting it) (Intentional Study) - فتحي على ميلاد محمد (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
ملخص هدفت الدراسة إلى التعرف على ظاهرة الهجرة غير الشرعية وفعالية الإجراءات والقوانين الليبية في مواجهتها. وتكمن مشكلة الدراسة في أن ليبيا تعاني من وجود الكثير من اللاجئين الغير شرعيين على أراضيها بشكل ملحوظ، وبالرغم من اتخاذ الدولة الليبية العديد من الإجراءات التي تحول دون المساس بسيادة الدولة الليبية وخرق القوانين واستغلال جماعات التهريب عبر الحدود البرية للوضع الأمني المتدهور منذ عام 2011 إلا أن المهاجرين غير الشرعيين مازالوا يعبرون الحدود البرية ومازالت هناك العديد من عمليات التهريب والإتجار بالبشر تحاول التدفق داخل الأراضي الليبية بالمخالفة لأحكام القانون لمحاولة الهروب إلى دول أوربا انطلاقاً من الأراضي الليبية مما يضع ليبيا أمام مأزق كبير ولاسيما أمام شركاءها الدوليين. وتبرز أهمية الدراسة في تسليط الضوء على ظاهرة الهجرة غير الشرعية وتأثيرها على فعالية الإجراءات والقوانين الليبية والتعرف على مقاصد الشريعة في ظاهرة الهجرة غير الشرعية. تستخدم الدراسة المنهج التحليلي، حيث يساهم المنهج التحليلي في تحليل ظاهرة الهجرة غير الشرعية في ليبيا والتعرف على مقاصد الشريعة في مكافحة ظاهرة الهجرة غير الشرعية. وتقوم الدراسة باستخدام المنهج المقارن لمقارنة القوانين والإجراءات الليبية المطبقة خلال فترة إجراء الدراسة، كما يساهم هذا المنهج في مقارنة القوانين الليبية بنظيرتها في الدول التي نجحت في مكافحة ظاهرة الهجرة غير الشرعية. وتستخدم الدراسة المنهج التحليلي حيث يساهم المنهج التحليلي في تحليل ظاهرة الهجرة غير الشرعية في ليبيا والتعرف على مقاصد الشريعة في مكافحة ظاهرة الهجرة غير الشرعية. ولقد توصلت الدراسة إلى العديد من النتائج من بينها أن طاهرة الهجرة غير الشرعية تعد من أبرز الظواهر. Abstract The study aimed to identify the phenomenon of illegal immigration and the effectiveness of Libyan procedures and laws in confronting it. The problem of the study lies in the fact that Libya suffers from the presence of many illegal refugees on its territory significantly, and despite the Libyan state taking many measures that prevent compromising the sovereignty of the Libyan state and violating laws and the exploitation of smuggling groups across the land borders of the deteriorating security situation since 2011, but that Illegal immigrants are still crossing the land borders, and there are still many smuggling and human trafficking operations trying to flow inside Libyan territory, in violation of the provisions of the law, to try to escape to European countries from Libyan territory, which puts Libya in great trouble, especially in front of its international partners. The study highlights the importance of shedding light on the phenomenon of illegal immigration and its impact on the effectiveness of Libyan procedures and laws, and to identify the purposes of Sharia in the phenomenon of illegal immigration. The study uses the analytical method, where the analytical method contributes to analyzing the phenomenon of illegal immigration in Libya and to identifying the purposes of Sharia in combating the phenomenon of illegal immigration. The study uses the comparative approach to compare the Libyan laws and procedures applied during the period of conducting the study. This approach also contributes to comparing the Libyan laws with their counterparts in the countries that succeeded in combating the phenomenon of illegal immigration. The study reached many results, including that the pure illegal immigration is one of the most prominent phenomena.